Investigation of substitution limits and emissions of an in-line six cylinder diesel derived dual fuel engine - Mitchell, Robert, author; Olsen, Daniel, advisor; Marchese, Anthony, committee member; Smith, Gordon, committee member (Colorado State University. Libraries, 2017)
New drilling techniques have expanded the availability and decreased the cost of oil and natural gas. This has resulted in an increase in drilling activity. Historically, power for drilling and hydraulic fracturing operations is supplied by diesel engines. The power demand requires large quantities of diesel fuel to be trucked to the well site. In an effort to reduce operating costs and disturbances to neighboring communities, natural gas is being utilized in these processes. One approach for achieving this is using natural gas from the local pipeline and routing it to the engine intake to convert the engine to a dual fuel engine. Some of the natural gas is thereby substituted for diesel in the combustion process reducing diesel consumption. Natural gas costs average around one sixth of the cost on a diesel gallon equivalent and the pipeline reduces the number of truck-loads of diesel fuel. However, there are limits to the amount of natural gas that can be substituted for diesel. This work examines the different substitution limits that exist for natural gas-diesel dual fuel engines across their load range. A John Deere 6.8L Tier II diesel engine was converted to a dual fuel engine with a commercially available dual fuel retrofit kit. The dual fuel kit was originally commissioned as is typical of field operation based on the dual fuel kit supplier's previous commissioning experience. After the baseline commissioning, the dual fuel combustion process was examined with combustion pressure measurements and exhaust gas sampling. The testing showed engine knock caused by end gas auto-ignition limits substitution at high loads. High substitutions at low loads can cause governor instability but this limit exists beyond where the emissions levels become unacceptable. Two methods were also investigated for their effectiveness on extending the substitution limits. These were adjusting the diesel injection timing and air manifold temperature. Retarding the injection timing was able to increase substitution levels by approximately 4% at full load while avoiding engine knock. Lowering the air manifold temperature was more successful, increasing the substitution levels by around 10% compared to the baseline commissioning. Advancing the timing at low loads was not able to achieve any significant benefits in allowable substitution. Preheating the incoming charge was able to increase substitution levels by 20% at 25% load.
Keywords: dual-fuel; natural gas; substitution limits; dual fuel knock; diesel; substitution